Principal's Perception of the Performance of Teaching and Learning Teachers (Study in Beutong District, Nagan Raya Regency in 2022) - Syamsulrizal Syamsulrizal; Hardian Hardian; Muhammad Iqbal; Ari Ardiansyah; Eva Syahraini; Hayatul Ulfa; Muhammad Ronal Fahlevi (Departement of Mathematics Education, 2024)
Penjasorkes is an educational process that utilizes physical activities that are planned sequentially to develop and improve individual physical fitness of students within the framework of the national education system. This study aims to determine the extent of the performance of Penjasorkes teachers in the teaching and learning process in Beutong District, Nagan Raya Regency in 2022. This type of research is classified as qualitative descriptive research. The population in this study was all 17 principals. Given the limited population, the entire population is used as a sample. The sampling technique with Total Sampling is that the entire population is sampled. Data collection techniques are carried out by filling out questionnaires. The results of the research obtained in this study are the performance of Penjasorkes teachers in planning, implementing, evaluating and disciplined tasks in learning in Beutong District in the good category. This can be seen in general (88.24%) of teaching teachers make learning plans to be given to students and compile curriculum content standards as a reference or guideline in learning, formulate learning objectives, make teaching materials used relevant to learning objectives. In general (100%) Penjasorkes teachers conduct post tests to students. In general (88.24%) teaching teachers carry out learning evaluations according to a predetermined schedule, explain the material again and assign additional tasks to students as improvements, carry out teaching in the form of providing learning materials and carry out regular evaluations and provide grades to students objectively. In general (88.24%) teaching teachers come to school on time, carry out all the rules set by the school and complete the tasks given by the principal on time.